(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research article delves into the multifaceted realm of language games within phraseological units, with a particular focus on the representation of historical memory in French and Uzbek languages. Employing a comparative analysis, the study explores how puns and word games contribute to the creation of new phraseological units, showcasing the intricate interplay between linguistic playfulness and the preservation of cultural heritage. Examples from both languages illustrate the dynamic nature of these language games, shedding light on their role in expressing “historical memory.” The analysis not only highlights the linguistic nuances within French and Uzbek phraseology but also delves into the socio-psychological spirit of these two distinct linguistic communities. By uncovering the subtle complexities of language games, this research contributes to a deeper understanding of the interconnection between language, culture, and historical consciousness.